Central Protectionism in China: The "Central SOE Problem" in Environmental Governance. (18th August 2017) - Eaton, Sarah; Kostka, Genia
Abstract: This article examines the so-called "central State Owned Enterprise (SOE) problem" in China's environmental governance system, namely central SOEs' defiance of environmental regulation. We present evidence showing that, in the last decade, central SOEs have been the source of a large number of serious pollution incidents and have often failed to comply with environmental guidelines and regulations. Central SOEs in the electricity generation and oil and gas industries are particularly culpable, with six firms alone accounting for 62 per cent of all 2, 370 reported violations (2004–2016). We argue that a combination of "central protectionism" of state-owned national champions and insufficient regulatory capacity in the environmental bureaucracy have provided state firms under central management with both incentives and opportunities to shirk on environmental regulations. Yet, while the institutions of central protectionism are deeply rooted, countervailing forces within the complex Chinese state are also gaining momentum. In spite of the considerable regulatory challenges, officials in the environment bureaucracy display increasing resolve and ingenuity in trying to strengthen their enforcement capacity. 摘要: 本文检视了中国环境治理系统中所谓的 "中央企业问题", 即央企违反环保法规的现象。笔者将提供证据证明在过去十年中, 央企已成为大量严重污染事故的始作俑者, 而且常常无法遵守环境保护的指导方针和法律法规。发电、石油和天然气行业中的央企尤其难辞其咎, 在 2004 年到 2016 年上报的 2370 起违规事件中, 单单 6 家这些行业中的央企就占了62%。笔者认为, 对国家重点企业的 "中央保护主义" 以及环保机构监管能力的不足, 使得在中央管理下国有企业既有动机也有机会逃开环保法规的制约。然而, 尽管中央保护主义的机制根深蒂固, 其对抗力量在中国复杂的国家政治中也蓄势待发。尽管监管上面临着艰巨挑战, 环保机构的官员展现了他们在增强自身执法能力上日益增长的决心和智慧。